Spontaneous Regression of Uterine Arteriovenous Malformations with Conservative Management - Keiko Mekaru; Sugiko Oishi; Kozue Akamine; Chiaki Heshiki; Yoichi Aoki (Case Reports in Obstetrics and Gynecology)
Uterine arteriovenous malformation (AVM) can cause massive hemorrhage and is often treated with uterine artery embolization (UAE), which may lead to ovarian insufficiency. Thus, avoiding UAE should be considered, particularly in women undergoing fertility treatments. We present three women diagnosed with postmiscarriage AVM on color Doppler by transvaginal ultrasound imaging. They had no genital bleeding and a small mass, measuring 16–22 mm. If estradiol was >300 pg/mL when AVM was diagnosed, then a gonadotropin-releasing hormone agonist was administered. All three women underwent follow-up observation, revealing spontaneous mass disappearance. To avoid ovarian insufficiency risk with UAE, conservative management and close follow-up observation should be considered in patients with AVM without bleeding, particularly during the fertility treatment.